Study of the waste disposal effect on air quality: the Italian case study. (23rd August 2022) - Lotrecchiano, Nicoletta; Ciampa, Renato; Giuliano, Aristide; Sofia, Daniele
The environmental status is defined by the combination of information about air pollution and waste production and management. This paper aims to compare the percentage of waste disposal in Italy with air quality. For each Italian region, the percentage of waste disposal and air quality were analysed. For some more interesting regions like Trentino South-Tyrol, Piedmont, Veneto, Lombardy, Lazio, Marche, Umbria, Abruzzo, Campania, Basilicata, Apulia, and Sicily relationship were highlighted taking into account citizens' concerns about air quality. It is clear, after analysing the data, that in 2012-2017 the environmental awareness of the Italian population has increased with a consequent increase in the percentage of waste disposal and with the improvement of air quality.